An applied study analyzing the relationship between organizational symmetry and achievement motivation -The second specialized dental center in Babylon - Al-Salami, Yamama Mudhher Azawi (Journal of Economic, Administrative and Legal Sciences, 2022)
Organizational symmetry is one of the recent topics for researchers in the behavior of organizations as it contributes to the balance of the organization due to its dimensions of positive behaviors that benefit the organization and its employees. On achievement and analysis of the relationship between them by measuring the three dimensions of organizational symmetry (Membership, similarity, loyalty) and its relationship to the motivation of workers to achieve, the research was applied to a sample of (55) single employees of the Second Specialized Dental Center in Babylon Governorate, where a questionnaire was used to identify the answer of the research sample about the variables that are studied and researched. The results showed that the respondents’ perceptions of organizational symmetry It was high, and their motivation for work and achievement is also high, and organizational symmetry is related to the dependent variable, and there is a statistically significant relationship between the independent variable and the dependent variable, in addition to the fact that the research sample employees enjoy a high level of membership and loyalty, and their goals are similar to those of their organization The more the organization is organizationally similar, the higher the performance of the workers and the more motivated the workers to complete the tasks assigned to them,. The research reached several recommendations, including giving opportunities to workers to participate in decision-making, in addition to paying attention to their abilities and skills, which creates a desire to improve their performance and increase their motivation to complete the tasks assigned to them.